SISTEM INFORMASI ADMINISTRASI DATA KEPENDUDUKAN PADA KANTOR KELURAHAN KOLURSARI - Erri Wahyu Puspitarini; Majida Noviyanti; Asmania DewiIndria Winata (STMIK YADIKA BANGIL, 2018)
Problems in the district office Kolursari is manual population data administration system cause inefficiency in processing, data retrieval and archiving letters, so we need a system that is expected to help solve the problem. This research focuses on two things: the population administration and the creation of multiple certificate. Based on system testing was done using a black-box testing which resulted in an average success rate.Keyword : Data, Population Administration, Black-box Testing.